2017
DOI: 10.31227/osf.io/aehfu
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Partisipasi Masyarakat Dalam Penyusunan Rencana Pembangunan Jangka Menengah Daerah (Rpjmd) Kota Pekanbaru 2012-2017

Abstract: Status: Postprint di Jurnal PUBLIKa Jilid 2 Terbitan April dan Oktober Halaman 48-58The region authority to controlling the development planning contained in a regulations No. 25 of 2014 about the system of development planning. The regulation give an opportunity to the public to become involved in every process of development especially in the long-term process, medium-term although short-term. Medium-term development plan (RPJMD) become the important ones to every region especially Peknbaru city, because th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
0
6
0
5
Order By: Relevance
“…According to Breinkerhoff, one level of participation is to conduct consultations and collaborate on joint activities. Consultation is a two-way exchange of information and views which also includes information dissemination and gathering feedback and reactions (Yandra, 2016).…”
Section: Dealing With Anomaly Voter Findingsmentioning
confidence: 99%
“…According to Breinkerhoff, one level of participation is to conduct consultations and collaborate on joint activities. Consultation is a two-way exchange of information and views which also includes information dissemination and gathering feedback and reactions (Yandra, 2016).…”
Section: Dealing With Anomaly Voter Findingsmentioning
confidence: 99%
“…Adapun yang menjadi informan sebanyak 9 orang yakni dari Kepala Sub Bagian Kepegawaian dan Pelayanan dan 8 staf kesekretariatan lainya. Untuk mendapatkan data yang tepat, peneliti menggunakan beberapa teknik pengumpulan data yakni wawancara mendalam, dokumentasi dan mengumpulkan data beserta membuat kesimpulan (Yandra 2017). Kemudian data dianalisis menggunakan metode interaktif sebagaimana yang telah di kemukakan oleh Miles dan Huberman, bahwa kegiatan analisis terdiri dari tiga alur kegiatan yang terjadi secara bersamaan, yaitu reduksi data, dan penarikan kesimpulan atau verifikasi (Wulandari et al 2017).…”
Section: Metodeunclassified
“…The weak bureau cratic capacity will hinder the success of RPMJD programs, such as in the gap between the Plan and Implementation of the Pasuruan Regional Medium-Term Development Plan (RPJMD) 2013-2018 (Widiyanti, 2019), the Public Works Affairs Sector Program ofthe Anambas Islands Regency (Lestari, Rini, & Dwiyanti, 2018). From the perspective of participation, (Yandra, 2016) found that in the preparation of the Pekanbaru City RPJMD, this participation had not effective because the community was not involved from the start in the RPJMD Formulation so that the community was stillseen as a subject in development. It is also very similar to Yogyakarta, where the local government is very dominan twith its technocratic approach (Kamim, Amal, & Khandiq).…”
Section: Panasmentioning
confidence: 99%